Особливості голограмного сприйняття візуальної перспективи в архітектурі - Кузьмич, Василь; Kuzmych, Vasyl (Видавництво Львівської політехніки, 2020)
Стаття присвячена явищу голограмного сприйняття людиною в аналізі архітектурного середовища. Включає в себе аспекти перспективно-тонального сприйняття візуальних факторів голограмного сканування зорового апарату людини. Спрямована на розуміння та відтворення особливостей та нюансів роботи зору, в контексті сумарного аналізу та відтворенню системи енергетичних потоків в елементах візуального сприйняття. Голограмний фактор сприйняття дійсності базується на різниці роботи правого та лівого ока, з особливістю кутового налаштування зору на об’єкт спостереження. Домінантною залишається лінія обрію чи висота сприйняття об’ємів, а також положення просторів архітектурного середовища.

The article is devoted to the phenomenon of holographic human perception in the analysis of the architectural environment. Includes aspects of perspective-tonal perception of visual factors of holographic scanning of the human visual system. Aimed at understanding and reproducing the features and nuances of vision, in the context of summary analysis and reproduction of the system of energy flows in the elements of visual perception. The holographic factor of perception of reality is based on the difference between the work of the right and left eye, with the peculiarity of the angular adjustment of vision to the object of observation. The horizon line or the height of the perception of volumes, as well as the position of the spaces of the architectural environment remain dominant. The purpose and objectives of the article are to adapt the understanding of stereoscopy – the perception of the hologram of the reproduction of the three-dimensional environment, and its application in architectural design. Specificity and originality of the chosen topic in the field of architecture, aimed at a better visual perception of the means and techniques of architectural and functional subordination, where along with ergonomic and functional principles, the designer must solve visual and psychological problems. This is possible only when mastering the mechanisms and tasks of visual perception in architecture. Understanding the artistic value of an architectural object is based on a subconscious analysis of the spatial and holographic characteristics of reality. The relevance of information lies in the mechanism and process of expression of the principles of stereo image, in the problems of visual image, and the processes of architectural image presentation in the design of objects. The inseparability and inseparability of volumes from the existing environment is primary in the consideration of daily and annual lighting of architecture, which produces the subject features of a qualitatively adjective nature. The visual mechanism of perception of design processes is based on the principles of geometric-linear distances, which allow a specific orientation in space. The next important point is the orientation, territorially planned distances and sizes. Such a theory of hologram or stereoscopy, subconsciously develops evolutionarily, along with the spatial features of an artificially created series of linear-tonal perspective. Man is constantly trying to get the most information from the environment. At the same time, the evolutionary scheme of development of visual communications actively includes the factor of contour perception of the shape of the object. The anatomical and constructive structure of the human visual system is of special importance in the perception of the surrounding reality. Functionally, the spherical shape of the eye is of special importance, which through the lens is able to adapt energy flows that irritate the sensitive neurons of the fundus in a certain configuration. With a certain system of binoculars, we receive signals from two eyes, which are adapted in the visual center of the brain with the difference between stereo perception and holographic analysis. A design feature of this factor will be the difference in location of different temperature regimes. As a result of this approach, we obtain a three-dimensional image aimed at identifying and analyzing the form with the use of comparative characteristics of architectural objects. The hologram will depend on the axial distance between the viewer's eyes and the angle of focus on the object. This distance will affect the angular capture or volume of the observation volume. As the spatial distance from the viewer, the hologram effect will decrease and move from the volume analysis factor to the shape analysis factor, losing the properties of stereoscopy and hologram.
Features of holographic perception of visual perspective in architecture
Keywords: сумарні точки сходження; ефект стереоскопії; ефект просторової та перспективної стерео орієнтації; візуальне сприйняття; total points of convergence; the effect of stereoscopy; the effect of spatial and perspective stereo orientation; visual perception; 7.017.9